Observations on trials of potoclean® as a teat-dipping disinfectant - Ahmet Semacan; Uçkun Sait Uçan; S. Merve Temimhan; Ülküm Çizmeci (Eurasian Journal of Veterinary Sciences)
Mastitis, especially caused by contagious mastitis agents is the most prevalent cause of intra mammary infections (IMI) in Türkiye. Contribution to mammary hygiene by post milking teat dipping with disinfectants is evidenced to decrease mastitis. An environment and user friendly disinfectant was observed on new IMI in 10 lactating cows in the Faculty's Farm, Konya, in this study. Two cows with subclinical mastitis at the beginning of the observation were not diagnosed mastitis again after 60 day's post milking teat dipping by the test disinfectant (right quarters). More IMI occurred in the control group (left quarters). No mycotic and clinical mastitis were occurred after trial (by both control and test disinfectants) in any of the quarters. Skins of the quarters to which test disinfectant has been applied did not showed any alterations as evidenced clinically by during the trial, although it was not analyzed histo-pathologically. The test disinfectant by comparison with the control showed that it may have a potential to prevent mastitis as evidenced by this preliminary observation.